The Use of Slang on Tiktok Comments in East Kalimantan - Siti Nisrina Azzahra; Ida Wardani; Aridah; Maria Teodora Ping; Ventje Jany Kalukar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research seeks to investigate the study of slang discourse seen in the TikTok comment sections of East Kalimantan users. Slang is a kind of informal language that sounds very entertaining, trendy, and creative. Normally, the usage of the language is mostly by young people so that they can express their feelings, interact with others, and follow what is trending in the digital world. For this reason, this research aims to unveil what types of slang people use, its uses, and how it reflects identity and communication strategies. The research utilizes qualitative descriptive methodologies for data collection, which is gathered from TikTok comments and interviews conducted with eight users from East Kalimantan. The findings reveal that various etiquettes of slang are greatly influenced by both the world and local culture. Some popular terms include “anjay,” “gacor,” “slay,” and “rizz,” among others. Most users learn slang from TikTok and Instagram and extend it in a way that makes them sound modern, funny, or relatable. Slang also helps people feel part of a group and, at the same time, more quickly communicate their thoughts.